EXPOUNDING PROPHETIC BUILDING PRINCIPLES ON THE SITE LAYOUT RE-DESIGN OF CONTEMPORARY RESIDENTIAL NEIGHBORHOODS - Babangida, Hamza (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2019)
The prophetic building principles (PBP) in this paper refer to building precedents in which the prophet of Islam applied in the construction of various building typologies. This paper went a step further to demonstrate how they could be expounded in the site layout designs of contemporary housing neighborhoods to achieve a satisfactory environment for Muslims. A triangulation of literature search and case study methods were adopted as the guiding methodology. The case study was used to demonstrate how the PBP was expounded in the redesign of the site layout of the Sardauna housing estate in Katsina. The first PBP expounded in the redesign results in the introduction of Friday mosque, daily prayer mosques, and educational institutions, while the second was achieved through overall redesign of the initial layout from the gridiron to the cluster layout concept. The third PBP of promoting a classless community was achieved by placing residents of different socioeconomic status together within a cluster. The last PBP has affected the management of the ecosystem. It was achieved through the provision of multiple sources of water to sustain wildlife and plants, provision of additional walkways, reduced walking distances, and reduced tarred roads. This study shows that contemporary site layouts of residential neighborhoods could be designed in line with Islamic values and yet achieves universally acceptable design criteria.